Pengaruh Penambahan Kombinasi Benzyl Amino Purine dan Pepton Terhadap Pertumbuhan Planlet Anggrek Cattleya sp. - Frida Kunti Setiowati; Nina Aulia Rahmah (Universitas Negeri Malang, 2023)
Orchidaceae is one type of ornamental plant which is a leading commodity. Cattleya sp. are a potential type of orchid in terms of productivity and high economic value. Conventional Cattleya sp. cultivation is considered less effective because the number of tillers produced is very limited. Therefore an alternative Cattleya sp. cultivation is needed using plant tissue culture techniques or in vitro. The research objective is to determine the effect of the addition of the combination of BAP and peptone on the growth of orchid plantlets Cattleya sp. This experiment was conducted in the Plant Tissue Culture Laboratory of the Faculty of Mathematics and Natural Science Universitas Negeri Malang from August to November 2016. This study used a completely randomized design. The treatment was in the form of ½ MS medium added with a combination of Benzyl Amino Purine (BAP) and Peptone. The explant used was the protocorm of Cattleya sp. 1 month old with a size of ± 0.5 cm. Protocorm was inoculated as much as 10 protocorm on media treatment. The results showed that Peptone can affected the growth of Cattleya sp. plantlets. The ½ MS treatment with the addition of peptone produced the highest number of leaves and the highest plantlet height, while the ½ MS treatment without the addition of BAP and peptone produced the highest number of roots.